Growth and Yield Performance of Upland and Lowland Rice Varieties Under Narrow-Wide Row Planting Systems in East Nusa Tenggara, Indonesia - Oky Dwi Purwanto; Yulia Pujiharti; ‪Rizky Prayogo Ramadhan (Department of Agrotechnology, Universitas Muhammadiyah Yogyakarta, 2023)
Appropriate plant spacing and new superior rice varieties are essential factors in achieving high yields. This study aimed to evaluate rice varieties and jajar legowo planting systems that increase growth and yield during the dry season in East Nusa Tenggara. The research was arranged in a split plot in a randomized complete block design with two replications. The rice varieties (main plot) consisted of upland rice (Inpago 8 and Inpago 12) and lowland rice (Inpari 32 and Ciherang). The planting systems (sub-plot) consisted of a square system 20 cm × 20 cm, jajar legowo 2:1 (30 – 60) cm × 15 cm, jajar legowo 2:1 (25 – 50) cm × 12.5 cm, jajar legowo 2:1 (20 – 40) cm × 10 cm, and jajar legowo 4:1 (20 – 40) cm × 10 cm. The results indicated that Inpago 12 planted with the jajar legowo 2:1 (25 – 50) cm × 12.5 cm resulted in higher growth and yield than those planted with the square system. All tested varieties were not significantly different, while the planting systems were statistically different. The planting system of jajar legowo 2:1 (25 – 50) cm × 12.5 cm obtained higher growth and yield than other planting systems.